Wartości przekazywane i pielęgnowane przez matki w rodzinach wiejskich w okresie międzywojennym - Józefowicz, Anna (Karkonoska Państwowa Szkoła Wyższa, 2011)
In the Polish Second Republic, so in the country reborn after one hundred twenty three years of captivity, the role of a woman as a woman-mother, was significantly emphasized. Press, literature, researchers have proved that safety and order in the whole country depend on safety and order in individual families. The key notion became: „from education of a mother to education of a child”.
Keywords: matka; rodzina; Druga Rzeczpospolita; wartości; praca; komunikacja; edukacja; wartości patriotyczne